Heterogeneity in progression of prodromal features in Parkinson's disease. (July 2019) - Schrag, A.; Zhelev, S.S.; Hotham, S.; Merritt, R.D.; Khan, K.; Graham, L.
Abstract: Background: In the pre-diagnostic phase of Parkinson's disease (PD), a range of motor and non-motor symptoms can occur. However, there is considerable variability in their onset and currently little information exists on the pattern of progression of clinical features before diagnosis. Methods: We analysed data from a survey amongst patients with PD from 11 European countries by the European Parkinson's Disease Association. They completed questions on first occurrence of 21 pre-diagnostic features. A principal component analysis (PCA) with varimax rotation was performed to determine the co-occurrence of these features. Findings: 1467 patients were included. Changes in movement were the most commonly reported features up to 4 years before diagnosis. However, at five or more years before diagnosis loss of sense of smell, sleep problems, fatigue and other non-motor features had been experienced most frequently. PCA of pre-diagnostic features' duration revealed three factors with eigenvalues over Kaiser's criterion of 1: a) a neuropsychiatric factor comprised of anxiety, depression, apathy, stress, and sleep problems; b) an axial factor defined by difficulty eating and/or swallowing problems, freezing, and falls/balance problems; and c) a motor factor with additional non-motor features. Bladder/bowel problems and tremor had low factor loadings on all components. However, in those with disease duration less than 5 years the autonomic features were associated with the axial factor and tremor loaded on both the motor and psychiatric symptom factors. Interpretation: The identified symptom complexes in the pre-diagnostic stage of PD may be reflective of a shared pattern of pathological disease progression. Highlights: There are at least three distinctive symptom complexes in prediagnostic Parkinson's. Non-motor symptoms are most common prodromal features beyond 4 years before diagnosis. Complexes may be reflective of a shared pattern of pathological disease progression.